Forced-Voluntary Return: An Intersectional Approach to Exploring "Voluntary" Return in Toronto, Canada. Issue 1 (1st June 2022) - Aberman, Tanya
Abstract: During the near decade of Conservative rule in Canada from 2006 to 2015, anti-refugee and anti-migrant discourse was continuously circulated by government officials. Social, economic, and physical restrictions were implemented based on the dichotomy of "deserving" versus "undeserving" migrants, and borders were created within communities. This article takes an intersectional approach to explore the reasons that some migrants chose to leave Canada "voluntarily" during that time, and the factors that forced them to do so. I offer the concept of forced-voluntary return to capture some of the tensions and messiness within migrant experiences that are neither completely voluntary nor forced. These tensions affirm the emerging calls in research to conceptualize migration on a spectrum from forced to voluntary, and contribute to understandings of migration management, the production of deportability, and the "voluntary" mobility of migrants by highlighting some of the ways in which intersecting identities impact migrants' decisions about return.